Traditional healers working with primary care and mental health for early intervention in psychosis in young persons: protocol for the feasibility cluster randomised controlled trial - Christian Mallen; Saima Sheikh; Martyn Lewis; Muhammad Firaz Khan; Lisa Dikomitis; Saeed Farooq; Nusrat Husain; Muhammad Irfan; Imran Chaudhry; Mian Mukhtar Ul Haq; Abdul Jalil Khan; Noor Sanauddin; et al. (BMJ Open, 2023)
Objectives In low/middle-income countries (LMICs), more than half of patients with first-episode psychosis initially seek treatment from traditional and religious healers as their first care. This contributes to an excessively long duration of untreated psychosis (DUP). There is a need for culturally appropriate interventions to involve traditional and spiritual healers to work collaboratively with primary care practitioners and psychiatrists through task-shifting for early detection, referral and treatment of first episode of psychosis.Methods To prevent the consequences of long DUP in adolescents in LMICs, we aim to develop and pilot test a culturally appropriate and context-bespoke intervention. Traditional HEalers working with primary care and mental Health for early interventiOn in Psychosis in young pErsons (THE HOPE) will be developed using ethnographic and qualitative methods with traditional healers and caregivers. We will conduct a randomised controlled cluster feasibility trial with a nested qualitative study to assess study recruitment and acceptability of the intervention. Ninety-three union councils in district Peshawar, Pakistan will be randomised and allocated using a 1:1 ratio to either intervention arm (THE HOPE) or enhanced treatment as usual and stratified by urban/rural setting. Data on feasibility outcomes will be collected at baseline and follow-up. Patients, carers, clinicians and policymakers will be interviewed to ascertain their views about the intervention. The decision to proceed to the phase III trial will be based on prespecified stop–go criteria.Ethics and dissemination Ethical approval has been obtained from Keele University Ethical Review Panel (ref: MH210177), Khyber Medical University Ethical Review Board (ref: DIR/KMU-EB/IG/001005) and National Bioethics Committee Pakistan (ref no. 4-87/NBC-840/22/621). The results of THE HOPE feasibility trial will be reported in peer-reviewed journals and academic conferences and disseminated to local stakeholders and policymakers.Trial registration number ISRCTN75347421.